Registration and tax policy of the German authorities regarding dogs in the Reichskommissariat «Ukraine» and methods of its implementation (1941–1943) - Ovsinskyj, Jurij (Ukrainian Peasant, 2024)
The purpose of the article is to highlight the registration and tax policy of the German authorities in the Reichskommissariat «Ukraine» (hereinafter – RKU) in 1941–1943 in relation to dog owners, based on the discovered sources; outline of the circle of administrative and executive bodies responsible for its implementation on the ground; characteristics of the registration process itself and the conditions for issuing registration tokens for dogs; clarification of the amounts and terms of payment of tax for dogs, as well as the dynamics of tax rates, preferential and exempt categories. The public reaction to this tax is randomly analyzed, in particular, the partial opposition of the population. Related to the topic, individual sanitary and veterinary prescriptions and social norms regarding the keeping of dogs are considered. The scientific novelty lies in the fact that although a lot has been written and published about the tax policy of the Third Reich in the occupied territories, in particular regarding Ukraine, this aspect of it has never been considered separately and deeply. Also, for the first time, a number of published sources (resolutions, orders, and orders of the occupying power of the RKU) related to the issues raised in the article were studied and introduced into scientific circulation. Conclusions. In 1941–1943, the RKU was established on part of the Ukrainian lands occupied by the Third Reich. The German authorities revived the practice of a tax on dogs from the population, which existed before that in the USSR. The reason for this was the need to record and register animals due to a significant number of stray dogs and frequent outbreaks of plagues, including rabies. The dog was registered by local authorities in the appropriate book, in which data about the owner of the animal, address, breed and sometimes the nickname of the dog were entered. The owner was issued a registration receipt, and the registration number attached to the dog was duplicated on the issued dog tag attached to the collar. At the initial stage (August-December 1941), the administration of the RKU in Rivne pursued a flexible tax policy, leaving the tax-tariff initiative regarding this and other types of taxes to the discretion of the local administration. As evidenced by the discovered and analyzed sources, in 1942-1943, the city, district and district administrative apparatus often adjusted the size of the tax on dogs in the direction of its increase or decrease according to circumstances or need. Since the peasants were reluctant to pay this tax (and in some cases even flatly refused to do so), due to the excessive tax burden and exhaustion of the peasant farms during the previous Soviet era, this sometimes forced local authorities to temporarily suspend tax collection or revise tax rates. After the offensive of the Soviet troops and the liberation of most of the occupied Ukrainian lands in 1943–1944, the German tax legislation lost its validity here. Evidence of dog registration and tax tokens from Ukrainian cities of this period was preserved only in published prescriptions and regulations, while the author is not aware of a single copy of such a token from the territories of the RKU in 1941–1943.